Predictors of worsening food security among women living with and without HIV and seronegative women during COVID-19: a mixed methods study - Jenni M. Wise; Hilary Bethancourt; Torsten B. Neilands; Anna Leddy; Gypsyamber D’Souza; Mirjam-Colette Kempf; Janet M. Turan; Gina Wingood; M. Reuel Friedman; Jennafer Kwait; Lakshmi Goparaju; Mardge Cohen; et al. (Food Security, 2026)
This study aimed to assess the prevalence, severity, predictors, and lived experiences of food insecurity among women enrolled in the Women’s Interagency HIV Study in the USA in 2020, at the height of the COVID-19 pandemic. We hypothesized that pre-existing socioeconomic and health-related disparities would heighten the risk of worsening food insecurity during the pandemic. The 10-item US Household Food Security Survey was administered to participants three times between June and September 2020. Multilevel mixed-effects ordered logistic regression models were used to estimate the odds of worsening food security compared to pre-pandemic baseline data. Qualitative interviews were conducted among a subset of participants to add understanding of the lived experience of food insecurity during the pandemic, beyond what quantitative measures could provide. Among 1,506 women, 28% had marginal to very low food security at baseline, and between 13.6-17.3% experienced worsening food security during pandemic measures. Women with household incomes <$12,000/year were particularly vulnerable to worsening food insecurity, including those experiencing unemployment (OR: 2.06, 95% CI:1.36, 3.13), job loss (OR: 1.47, 95% CI: 1.04-2.06), loss of financial support (OR: 1.91,95% CI: 1.23, 2.97), and those with reduced access to usual sources of food (OR: 7.67, 95% CI:4.78, 12.30). While the quantitative data suggest that relatively few women experienced worsening food security during the pandemic, the qualitative data suggest that many more women had difficulty accessing preferred and healthy foods and experienced disruption to social services, which typically facilitate the ability to access food. Women described how informal social systems (e.g., neighborhood gardens, sharing resources) bridged the gap left by more formal systems during this time. Taken together, these findings suggest that women with pre-existing socioeconomic vulnerability were disproportionately and negatively impacted by the social and economic disruptions of the COVID-19 pandemic. Interventions are needed to address structural vulnerabilities, improve safeguards to food security during times of distress, and harness the capacity of community-based support systems.